O espaço sobrenatural representado em Montedemo de Hélia Correia - Moreira, Anamaria Pereira (2010)
This study aims to analyze the supernatural represented in Montedemo of writer Hélia Correia. The aim of this monographic study is to elucidate the categories linked to strange or supernatural (Fantastic, Wonderful, Wonderful Realism) and show that the classification of that work just as fantastic and arbitrary, according to new theories related to magical realism. The creation of a fictional work using this model is seen by the author's criticism as a form of writers of the time to create a narrative in which are unusual or unrealistic attempts to escape a real poor and banal. Thinking of a time that is recovering from a period of political repression, it is a form of immediate elaboration of Portuguese history, a symbolic restructuring, and that does not mean identity. In order to do this, this work entitled "The supernatural represented in works of Hélia Correia," proposes to address the fictional works of the author, during the 80s, trying to understand it from the requirements that are subject to English prose after April 25. The suggested reading, held from categories that govern the contemporary narrative, allows defining features of history in such works, still presented using a strong imaginary component anchored in the mystical vision of the world ports.